Seven Months after Mild COVID-19: A Single-Centre Controlled Follow-Up Study in the District of Constance (FSC19-KN) - Haberland, Elisabeth; Haberland, Jonas; Richter, Stephan; Schmid, Michael; Hromek, Julia; Zimmermann, Heidi; Geng, Sabrina; Winterer, Hannes; Schneider, Steffen; Kollum, Marc (International journal of clinical practice (Esher), 2022)
Importance. Viral infections can lead to prolonged recovery and secondary diseases among the survivors. Therefore, the management of post-coronavirus infectious disease 2019 (COVID-19) patients needs to be planned efficiently based on significant data. Despite numerous follow-up studies, there still is a lack of knowledge in this field. Objective. The primary aim of the study was to investigate the rate of hospitalization and admission diagnoses in severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) positive patients seven months after initial infection. Secondarily, measurement of long-term effects on physical performance, quality of life, and functional outcome was intended. Design. The study is designed as a controlled follow-up of COVID-19 cases in the district of Constance (FSC19-KN). Setting. A controlled setting is provided due to the recruitment of an equally sized cohort consisting of age- and gender-matched subjects featuring similar cardiovascular risk profiles and negative SARS-CoV-2 antibody titers. Participants. The study examines 206 subjects after polymerase chain reaction (PCR) confirmed SARS-CoV-2 infection seven months after initial infection. Exposure. Infection in the SARS-CoV-2 positive group occurred between March and December 2020. Main Outcome and Measures. The frequency of inpatient admission during the observational period including the related diagnosis was defined as the primary endpoint. Secondary endpoints were health-related quality of life, physical performance, and functional outcome measured by European Quality of Life-5-Dimensions-5-Level (EQ-5D-5L), Short Form Health 36 (SF-36), Six-Minute Walk Test (6MWT), and Post-COVID-19 Functional Status (PCFS). Results. The study population consisted of mainly nonhospitalized subjects. During the first seven months of observation, frequency of inpatient admission was low and did not differ significantly between both groups (2.4% vs. 2.9% controls: OR 0.8, 95% CI 0.2 to 2.8). Calculation of six-minute walk distance ratios showed no significant difference between both cohorts (0.97 ± 0.17 vs. 0.98 ± 0.16 controls; mean difference −0.01; 95% CI −0.04 to 0.02). However, SARS-CoV-2-positive subjects achieved significantly lower EQ-5D-5L index scores (0.92 ± 0.12 vs. 0.95 ± 0.1 controls; mean difference −0.03, 95% CI −0.05 to −0.01) and SF-36 subscores. Reduced PCFS was reported significantly more often in the SARS-CoV-2 positive cohort (30.6% vs 14.6% controls: OR 2.6, 95% CI 1.6 to 4.2). Conclusion. The results suggest that mild COVID-19 has no impact on the hospitalization rate during the first seven months after infection. Despite unimpaired performance in cardiopulmonary exercise, SARS-CoV-2-positive subjects reported reduced quality of life and functional sequelae. Underlying psychoneurological mechanisms need further investigation. Trial Registration. This trial is registered with clinicaltrials.gov (identifier: NCT04724434) and German Clinical Trials Register (identifier: DKRS00022409).